Association between Hemoglobin Glycation Index and NAFLD in Chinese Nondiabetic Individuals. (21st December 2019) - Hu, Di-Shuang; Zhu, Sheng-Hao; Li, Xu; Chen, Qin-Fen; Lin, Chun-Jing; Fang, Dan-Hong; Wu, Jian-Sheng
Abstract : Purpose . Limited studies have preliminarily identified a positive association between nonalcoholic fatty liver disease (NAFLD) and hemoglobin glycation index (HGI). However, this association has not been fully established. We aim to investigate the association between NAFLD and HGI in Chinese nondiabetic individuals and to construct a risk score based on HGI to predict a person's risk of NAFLD. Methods . After strict exclusion criteria, 5, 903 individuals were included in this retrospective cross-sectional study. We randomly selected 1, 967 subjects in the enrollment to obtain an equation of linear regression, which was used to calculate predicted HbA1c and drive HGI. The other subjects were classified into four categories according to HGI level (≤−0.22, −0.21∼0.02, 0.03∼0.28, and ≥0.29). All subjects retrospectively reviewed the baseline characteristics, laboratory examinations, and abdominal ultrasonography. Results . The prevalence of NAFLD in this population was 20.7%, which increases along with the growth of HGI levels (P < 0.001 ). Adjusted to multiple factors, this trend still remained significant (OR: 1.172 (95% CI, 1.074–1.279)). The combined NAFLD risk score based on HGI resulted in an area under the receiver operator characteristic curve (AUROC) of 0.85 provided sensitivity, specificity, positive predictive value, and a negative predictive value for NAFLD of 84.4%, 71.3%, 65.0%, and 88.0%, respectively. Conclusions . NAFLD is independently associated with HGI levels in Chinese nondiabetic individuals. And, NAFLD risk score may be used as one of the risk predictors of NAFLD in nondiabetic population.